Parma e la cultura ebraica Archivi da scoprire In occasione nel Giorno della Memoria 2013 (Parma, Archivio di Stato, 30 gennaio 2013) (Altre Modernità, 2013)
Since 1987, the history of Jewish culture in Parma has found new sources, when some fragments of Medieval Hebrew manuscripts were discovered in the State Archive (Archivio di Stato di Parma). In 2011, after more than twenty years, thanks to the cooperation among the Archivio di Stato di Parma, the Israel National Library-Institute of Microfilmed Hebrew Manuscripts, the Italian Association of the Friends of the Hebrew University of Jerusalem and the Ambrosiana Library, new researche projects have been established. As an outcome of this collaboration, fragments  of 54 manuscripts of Bible, Bible Commentaries, Midrash, Mishnah, Talmud, Halakhah and Liturgy have been examined. The result of these studies will be soon published.